2012
DOI: 10.1523/jneurosci.0267-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Guidance-Cue Control of Horizontal Cell Morphology, Lamination, and Synapse Formation in the Mammalian Outer Retina

Abstract: In the vertebrate retina, neuronal circuitry required for visual perception is organized within specific laminae. Photoreceptors convey external visual information to bipolar and horizontal cells at triad ribbon synapses established within the outer plexiform layer (OPL), initiating retinal visual processing. However, the molecular mechanisms that organize these three classes of neuronal processes within the OPL, thereby ensuring appropriate ribbon-synapse formation, remain largely unknown. Here we show that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 48 publications
1
60
0
Order By: Relevance
“…Recent studies have identified multiple repulsive signaling pathways that function in dendrite patterning of vertebrate and invertebrate neurons, including semaphorin/plexin (Polleux et al 2000;Matsuoka et al 2012;Sun et al 2013), Dscams (Matthews et al 2007;Soba et al 2007;Fuerst et al 2009), protocadherins (Lefebvre et al 2012), Netrin/DCC/UNC-5 (Smith et al 2012), and Slit/Robo (Furrer et al 2007;Gibson et al 2014). We thus examined potential roles of the repulsive factors in the ventral boundary specification of v'ada dendrites by using genetic mutants or RNAi knockdown, but, to our surprise, none of them showed obvious defects in v'ada dendrite boundary specification (Supplemental Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified multiple repulsive signaling pathways that function in dendrite patterning of vertebrate and invertebrate neurons, including semaphorin/plexin (Polleux et al 2000;Matsuoka et al 2012;Sun et al 2013), Dscams (Matthews et al 2007;Soba et al 2007;Fuerst et al 2009), protocadherins (Lefebvre et al 2012), Netrin/DCC/UNC-5 (Smith et al 2012), and Slit/Robo (Furrer et al 2007;Gibson et al 2014). We thus examined potential roles of the repulsive factors in the ventral boundary specification of v'ada dendrites by using genetic mutants or RNAi knockdown, but, to our surprise, none of them showed obvious defects in v'ada dendrite boundary specification (Supplemental Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Dscam or Dscaml1 function results in a soma and dendrite-clustering phenotype that superficially resembles a similar dendrite self-avoidance phenotype observed in Drosophila Dscam1 mutants (Zhu et al, 2006;Matthews et al, 2007). Dscam1 has been shown to actively drive avoidance through repulsion, which limits dendrites of a given cell from crossing other dendrites originating from the same cell (Hughes et al, 2007).…”
Section: Dscam and Dendrite Avoidancementioning
confidence: 93%
“…4). These results suggest that the role of mouse Dscam may be better reflected by some of the other Drosophila Dscams or phenotypes (Millard et al, 2010;Hutchinson et al, 2014), with the role of Drosophila Dscam1 in mouse likely provided by other molecules, such as the ␥-protocadherins (Lefebvre et al, 2008(Lefebvre et al, , 2012.…”
Section: Dscam and Dendrite Avoidancementioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, new concepts in this area are emerging quickly, including the demonstration of molecular control over outer retinal cell type tiling by guidance cue signaling. Kolodkin and coworkers (Matsuoka et al 2012) recently showed that the repellant guidance cues Sema6a and PlexinA4 are important for self-avoidance of horizontal cell processes. The independence of such phenotypes between specific retinal neuron subtypes and their expression of distinct ligands, receptors, and isoform profiles reinforces the idea that while mosaic spacing and tiling are ubiquitous features in retinal neurons, each retinal neuron subtype may employ a different set of molecular signals to achieve these key features of retinal organization.…”
Section: Cell Type Specification In the Mammalian Visual Systemmentioning
confidence: 99%